Pengaruh Pembelajaran Teknik Teka Teki Silang dan Motivasi Belajar Sejarah Terhadap Prestasi Belajar Siswa Kelas XI IPA SMAN 1 Bululawang Kabupaten Malang - Widayati Rahayu (Program Studi Pendidikan Sejarah Universitas Riau, 2021)
These studies analyze the impact of the learning of the learned and the puzzle silan of achievement student studying the history of science SMAN 1 Bululawang with questioner analysis of 30 the students finally found the linear regression analysis double processed using software spss for the window. Using a technique a crossword puzzle for teaching history can training for independent students in digging information on the history of various sources so that they would be more active and enthusiastic in attending the learning history, the motivation and learning activities in the history of studying would have seemed to improve achievement for a student. The results of testing against modeled on the research, capable of being explained influence between learning technique theca cyperus cross and the motivation to study for against achievement studying the history of a student of class XI IPA has yielded the conclusion that learning technique theca cyperus cross and the motivation to study for could affect the achievement studying the history of a student of class XI IPA SMAN 1 Bululawang. The result of this research is very important as there are the effects of each of the variables, namely independent variables to dependent variables.